Effect on Physiological Variables and Urinary Metabolites following a Single Dermal Application of Sulphur Mustard in Rats - Kumar, Om; Vijayaraghavan, R. (Defence Science Journal, 2013)
The effect of single dermal application of different doses of sulphur mustard (2,2'-dichlorodiethyl sulphide, SM), i.e.5, 10 and 20 mg/kg body weight on some physiological variables, viz., body weight, intake of food and water, and excretion of excreta and urine was studied for one week. Levels of urinary metabolites, uric acid, urea, protein, creatine and creatinine were measured at 0, 1, 2, and 7 days in albino rats of Wister strain. A progressive dose-dependent fall in body weight was observed from day onwards after SM application. Feed and water intake were reduced significantly. Excretion of urine and exdreta was also affected adversely. The level of uric acid, a metabolite of purine bases, increased 24 hr post-exposure, in a time and dose-dependent manner. Excretion of urea decreased and the level of creatine increased drastically on 7th day. However, urinary excretions of protein and creatinine did not change. The study shows that single application of SM in rats induces a catabolic state.